Response of fermions in Chern bands to spatially local quenches. (8th August 2016) - Grushin, Adolfo G; Roy, Sthitadhi; Haque, Masudul
Abstract: We study the dynamical evolution of Chern-band systems after subjecting them to local quenches. For open-boundary systems, we show for half-filling that the chiral nature of edge states is manifested in the time-dependent chiral response to local density quenches on the edge. In the presence of power-law traps, we show how to mimic the half-filling situation by choosing the appropriate number of fermions depending on the trap size, and explore chiral responses of edges to local quenches in such a configuration. We find that perturbations resulting from the quenches propagate at smaller group velocities as the gap controlling the spatial extent of the edge modes decreases. Our results provide different routes to check dynamically the non-trivial nature of Chern bands.